2017
DOI: 10.1001/jamapediatrics.2017.2135
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Adverse Events in Emergency Department Procedural Sedation for Children

Abstract: IMPORTANCE Procedural sedation for children undergoing painful procedures is standard practice in emergency departments worldwide. Previous studies of emergency department sedation are limited by their single-center design and are underpowered to identify risk factors for serious adverse events (SAEs), thereby limiting their influence on sedation practice and patient outcomes.OBJECTIVE To examine the incidence and risk factors associated with sedation-related SAEs.DESIGN, SETTING, AND PARTICIPANTS This prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
132
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(161 citation statements)
references
References 36 publications
14
132
3
5
Order By: Relevance
“…Only two pediatric studies have examined the relationship between adverse events and opioid administration prior to ED sedation and to our knowledge there are no studies that have assessed the impact of timing of opioid administration. In our cohort of 6,295 patients, we demonstrated that opioids administered prior to sedation were significantly associated with oxygen desaturation, need for PPV, and vomiting . In a retrospective, unadjusted analysis of a smaller number of ED ketamine sedations ( n = 858), Waterman and colleagues detected no difference in the incidence of adverse events between those patients who did and did not receive preprocedural opioids.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Only two pediatric studies have examined the relationship between adverse events and opioid administration prior to ED sedation and to our knowledge there are no studies that have assessed the impact of timing of opioid administration. In our cohort of 6,295 patients, we demonstrated that opioids administered prior to sedation were significantly associated with oxygen desaturation, need for PPV, and vomiting . In a retrospective, unadjusted analysis of a smaller number of ED ketamine sedations ( n = 858), Waterman and colleagues detected no difference in the incidence of adverse events between those patients who did and did not receive preprocedural opioids.…”
Section: Discussionmentioning
confidence: 62%
“…Characteristics of children included in the study are presented in Table . Of the 6,295 sedations included in the final analysis of the parent study, 1,806 (29% of the original cohort) received a preprocedural opioid. Of those who received an opioid, 1,255 (69.5%) patients received morphine, 523 (29.0%) received fentanyl, and 8 (0.4%) received hydromorphone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Langston et al 1 demonstrated that ondansetron significantly reduces emesis in children of all ages undergoing intravenous ketamine procedural sedation, with an NNT of 8 in children older than 5 years, although this subanalysis has a wide CI. Bhatt et al 2 have shown in a multicentre, prospective cohort study that the use of antiemetic is associated with a reduced rate of vomiting in ketamine procedural sedation. This study also showed that the use of preprocedural opioids is associated with a higher rate of emesis during ketamine sedation in children.…”
Section: Commentsmentioning
confidence: 99%